Gravimetric transect of eastern Ungava Bay, northern Torngat Orogen. - Seguin, Maurice; Goulet, Normand (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Abstract Detailed gravity data, collected in the northern part of Québec along a SW-NE transectacross the northern Torngat Orogen, provide constraints on the deep structure of this segment of the orogen. The section, located inthe Rae Province east of Ungava Bay, traverses the Archean gneissic terrane of theGeorge River segment, the Early Proterozoic metasedimentary rocks of the Lake Har-bour Group, the Abloviak shear zone and thegranullte-facies migmatttlc complex of the Burwell terrane. The Bouguer gravity profile indicates four distinct zones: (1) in the SW, a low density zone from George River to theeast of Keglo Bay; (2) a zone of intermediate density further to the NE from the Lake Harbour Group extending to Abloviak Fiord; (3) a steep, narrow, Bouguer gravity gradient {positive to the N) which is prominent along the Abloviak shear zone; and (4) a high density zone in the extreme NE of the area. The gravity trend on the contoured Bouguer gravity map is NE in zones 1 and 2, where as it is E-W in zones 3 and 4 and could be correlated with a similar trend in the northern part of the Superior Province west of Ungava Bay. Short wavelength anomalies in zone 1indicate the presence of basin-and-domestructures in the gneissic terrane.